At The Intersection of Justice and Faith - Allison Gammons (Theological Librarianship, 2021)
Religious leaders involved in social justice activities (SJC) exist at the junction of two information communities—religious leaders and social justice activists—possessing unique information needs and information-seeking behaviors. There are no existing studies focusing on the information needs of SJC, but much can be gleaned from the explorations around the information seeking behaviors of clergy, religious leaders, and activists. SJC information behaviors can be viewed through the lens of a variety of information systems and frameworks but particularly within the encountering of information in information grounds. Due to the diversity of SJC, many of their information grounds exist in online communities utilizing social media sites such as Twitter and Facebook. There is a need for further research on the information-seeking behaviors of SJC, to further understand their information needs so information professionals can provide better assistance to this unique information community.